If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2z+5=4z-9
We move all terms to the left:
2z+5-(4z-9)=0
We get rid of parentheses
2z-4z+9+5=0
We add all the numbers together, and all the variables
-2z+14=0
We move all terms containing z to the left, all other terms to the right
-2z=-14
z=-14/-2
z=+7
| 11x-18=8x+11 | | 12p-12p+2p=4 | | -3+x=21/2 | | x^2=31-x^2 | | 13b-11b-2b+3b=18 | | 16q-15q+2q+3q-4q=18 | | 10y-6=3y+8 | | (x-4)(x-3)2=x-7x+12 | | 16q−15q+2q+3q−4q=18 | | 2x=15−x | | 7s−3s=12 | | 67=-3y=16 | | 10h+10h=20 | | 5g-3g=16 | | 3p+3p=12 | | 5(x-3)-2(x+1)=3 | | 5x+2/3+1=10 | | 3×2^x=60 | | x2=31−x2 | | -4x/3=-20 | | 2x^2+2x=8-6x | | (4-3x)^2=23 | | (4/n-4)-(3/n-2)=0 | | 2x=150+x | | 5(4h-1)=6h+2 | | 125x-2=5-x | | 3(x-2)/4-2(x+1)/5=3/10 | | 12x-84=x-3 | | 2x-4=x+48 | | x9+9=15 | | x8=15 | | 2/3x-1/4=1/2 |